(untitled) (Revista Brasileira de Computação Aplicada, 2016)
This paper presents a cultural entertainment game entitled “Rota do Tropeiro”. The aim of our article is to briefly present well-known tools that can be integrated and used by beginners to develop games with quality and optimized performance, especially for the Android platform. The document describes our game prototype, showing techniques and methodologies applied and highlighting new challenges. As a result, we produced a mobile game for end-users, and creative stuffs like animations, geometric models and artificial intelligence scripts.